(untitled) (Interdisciplinary Studies Journal, 2024)
The beginning of 2020 was marked by the COVID-19 pandemic among humans, seriously affecting people’s global health. Since the beginning of the pandemic, health authorities have demonstrated how disastrous the magnitude of the uncertainties and consequences could be across the world. Objective: Investigate and describe the perception of Brazilian interpersonal relationships during the COVID-19 pandemic in the face of preventive measures against the spread of the virus in the country. Methodology: Descriptive cross-sectional epidemiological study carried out by an international consortium of scientists from different countries. An online questionnaire was used to collect data, with questions about how COVID-19 affects daily life. Eligible individuals needed to be adults aged 18 or older. The study was carried out from February 2020 to November 2022. Results: The majority considered that the country’s pandemic situation was out of control or completely out of control (48.4% and 37.3%, respectively). Regarding concerns about COVID-19, around 23% have not coped well. More than three thirds of the participants reported good control of their alcohol consumption, as opposed to around 9%, who did not control their alcohol consumption well. 32%, who reported not making good use of their time. Conclusions: The promotion of effective actions and efficient public policies with regard to guidance, prevention and treatment aimed at mental health problems in health emergency situations is notable. Keywords: COVID-19; Pandemic; Interpersonal relationships.